Journal: 100 Years / In The Circuit Court of the United States For The District Of Delaware United States of America, Petitioner vs E.I. DuPont De Nemours and Company and Others, Defendants July 13, 1907 Origin of the Conspiracy and the Various - Robert Hopler (International Society of Explosives Engineers, 2008)
That some time in the year 1872 there was organized an association composed of practically all of the manufacturers of gunpowder and other high explosives in the United States, the members of which said association were as follows: E. I. du Pont de Nemours & Co., The Hazard Powder Company, Laflin & Rand Powder Company, Oriental Powder Mills, American Powder Company, The Miami Powder Company, and Austin Powder Company of Cleveland, all of which or their successors are defendants herein; that the object and purpose of said association was the elimination of all competition between the members thereof in the shipment and sale of gunpowder and other high explosives among the various States and Territories of the United States; that the only manufacturers of gunpowder and other high explosives which did not join such association at the time of its organization were the California Powder Works, The Sycamore Manufacturing Company, and The Lake Superior Powder Company, but your petitioner alleges that each of said three last named companies